2014
DOI: 10.1111/lasr.12102
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of the Legitimacy of the Law and Legal Authorities: Evidence from the Caribbean

Abstract: Research on procedural justice and legitimacy has expanded greatly across the social sciences in recent years. The process-based model of regulation, which links people's assessments of procedural justice and legitimacy to their compliance with the law and legal authorities, has become particularly influential in criminology and sociolegal studies. A review of the previous research on perceived legitimacy highlights two important features. First, legitimacy has been conceptualized and measured in many differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 67 publications
2
122
1
3
Order By: Relevance
“…On the other hand, we offer a richer account of the normatively salient aspects of policing to contribute to ongoing debates about the nature of legitimacy (Reisig et al 2007;Bottoms and Tankebe 2012;Tyler andJackson 2013, 2014;Gau, 2014;Johnson et al, 2014). Originally, Tyler (2006) treated legitimacy as a combination of institutional trust and duty to obey.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we offer a richer account of the normatively salient aspects of policing to contribute to ongoing debates about the nature of legitimacy (Reisig et al 2007;Bottoms and Tankebe 2012;Tyler andJackson 2013, 2014;Gau, 2014;Johnson et al, 2014). Originally, Tyler (2006) treated legitimacy as a combination of institutional trust and duty to obey.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it bears reiterating that there are more dimensions of various forms of motivations than those measured in this study (Johnson et al, 2014). For example, legitimacy can be measured in terms of both the obligation to obey and support for the authorities.…”
Section: Implications For Researchmentioning
confidence: 99%
“…As mentioned, legitimacy is a more encompassing term than simply the obligation to obey; studies have also shown that support for authorities is indicative of legitimacy (Johnson et al, 2014). In addition, expected benefit could not be measured to fully reflect instrumental motivation; the latent variable for instrumental motivation only concerns the relative convenience of local vehicles.…”
Section: Motivation Constructs and Compliance Variable Representationmentioning
confidence: 99%
“…A number of scholars have argued that procedural justice research inconsistently operationalises key constructs and has done little to evaluate the construct validity of existing scales (for example, Gau 2011; Reisig et al 2007;Johnson et al 2014). These authors have noted that measures of procedural justice and police legitimacy have differed from one study to the next.…”
Section: Controversies In the Fieldmentioning
confidence: 99%